Development of Learning Guide Based on Parental Involvement Model in Early Childhood Learning Through Distance Learning - Afri Dewita; Zelhendri Zen (International Journal of Educational Dynamics, 2022)
The implementation of distance learning (PJJ) with the learning from home strategy, is one option in implementing learning involving parental participation. This study aims to create and develop a learning guide for parents that can be used to support distance learning through learning from home strategies, thereby helping parents understand the right way of learning to accompany their children during the distance learning process. This handbook can open up parents' insight about how to carry out learning at home and what items can be used as learning media. This learning guide book is made using behavioristic learning strategies with parental involvement learning models, combining traditional and creative games into the learning process.